2005
DOI: 10.1007/s00223-005-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Copper Supplementation on Deposition of Fluoride in Bone in Fluoride- and Molybdenum-Fed Rabbits

Abstract: Fluorosis is a major public health problem in the world, including India. The present study was undertaken to investigate the role of molybdenum (Mo) in the deposition of fluoride (F) in bone and whether copper (Cu) supplementation has any alleviating role when F and Mo are ingested together. For this purpose, four groups of rabbits were used [control (C), fluoride (F), fluoride + molybdenum (F + Mo), and fluoride + molybdenum + copper (F + Mo + Cu)] to find out the effect of these treatments on various bone-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Increased utilization of zinc and copper for counteracting fluoride-induced oxidative stress may also be, at least partially, responsible for decrease in blood level of these elements. This is substantiated by the observation that supplementation of Zn, Cu and other antioxidant minerals like selenium have beneficial effects in fluoride intoxication (Liu and Kang 2003;Han-Bo et al 2001;Khandare et al 2005b). Bhargavi et al (2004) reported that lower concentration of Ca, Cu and Mg in drinking water was associated with increased prevalence of dental fluorosis in man.…”
Section: Resultsmentioning
confidence: 84%
“…Increased utilization of zinc and copper for counteracting fluoride-induced oxidative stress may also be, at least partially, responsible for decrease in blood level of these elements. This is substantiated by the observation that supplementation of Zn, Cu and other antioxidant minerals like selenium have beneficial effects in fluoride intoxication (Liu and Kang 2003;Han-Bo et al 2001;Khandare et al 2005b). Bhargavi et al (2004) reported that lower concentration of Ca, Cu and Mg in drinking water was associated with increased prevalence of dental fluorosis in man.…”
Section: Resultsmentioning
confidence: 84%
“…Uma vez que não houve incremento na peroxidação lipídica, também não houve necessidade de uma resposta adaptativa por parte da GS. Segundo CHLUBEK (2003) KHANDARE et al (2005), analisando amostras sangüíneas de coelhos tratados com 150ppm de F na água de beber, observaram decréscimo do teor de Cu. Ambos os elementos analisados (Cu e Zn) são essenciais para a formação da enzima antioxidante superóxido dismutase (SOD).…”
Section: Resultsunclassified
“…Fluorosis is a common health problem in animals as well as in human being in the world (Khandare et al 2005). Now a day, industrial fluorosis has become very common due to intensive production systems, mechanization in agriculture and industrialization, that leads to pollution of water and vegetation with fluoride (Chinoy 1993).…”
Section: Introductionmentioning
confidence: 99%